Peningkatan Inovasi Guru Melalui Penguatan Kepemimpinan Situasional Dan Motivasi Berprestasi Guru - Nugraha, Ujang Parah; Sunaryo, Widodo; Muharam, Hari (Universitas Pakuan, 2023)
IMPROVING TEACHER INNOVATION THROUGH STRENGTHENING SITUATIONAL LEADERSHIP AND ACHIEVEMENT MOTIVATIONThis study aims to determine the strength of the relationship between Situational Leadership and Teacher Innovation, the strength of the relationship between Achievement Motivation and Teacher Innovation, and the strength of the relationship between Situational Leadership and Achievement Motivation together with Teacher Innovation. This research was carried out in Madrasah Ibtidaiyah Se Region I Cianjur Regency which involved 124 Madrasah Teachers. The research method used in this research is the correlational method which is part of the type of quantitative descriptive research. The submission of the hypothesis uses parametric statistical analysis in the form of simple and multiple linear regression analysis, the analysis uses a significance level of a = 0.01 and a = 0.05. There is a very significant positive relationship with a very strong relationship strength between the Situational Leadership variable (X1) and Teacher Innovation (Y) which is indicated by linear regression = 24.16+ 0.80X1. The correlation coefficient (ry1) is 0.848 and the determination coefficient (Ry12) is 0.719. There is a very significant positive relationship with a very strong relationship strength between the variable Achievement Motivation (X2) and Teacher Innovation (Y) which is indicated by the linear regression equation = 29.99 + 0.76X2. The correlation coefficient (ry2) is 0.858 and the determination coefficient (Ry22) is 0.736. There is a very significant positive with a very strong relationship strength between Situational Leadership and Achievement Motivation variables together with Teacher Innovation as indicated by the linear regression equation = 24.01 +0.34X1 +0.46X2. The value of the correlation coefficient (ry.12) is 0.967 and the coefficient of determination (Ry.12) is 0.936. Based on the results of the study, it was stated that the Innovation of Madrasah Ibtidaiyah Teachers in Region I Cianjur Regency could be improved by strengthening Situational Leadership and Achievement Motivation.